2006
DOI: 10.1507/endocrj.k06-011
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) Effects on Central Fat Accumulation in Adult Japanese GH Deficient Patients: 6-month Fixed-dose Effects Persist during Second 6-month Individualized-dose Phase

Abstract: Abstract. Both Japanese and Caucasian adults with GH deficiency (GHD) have pronounced abdominal obesity, which is associated with increased risk of cardiovascular complications. We investigated the effects of GH treatment in 27 adult Japanese GHD patients, 15 with adult onset (AO) and 12 with childhood onset (CO) GHD. Patients initially received GH titrated to 0.012 mg/kg/day for 24 weeks in a double-blind design and the dose was then individualized for each patient according to IGF-I for a further 24 weeks. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Abnormal central fat accumulation was recently reported to be reduced by growth hormone treatment, which would result in cardiovascular risk reduction at the optimal dose. 10 In conclusion, our study found that the intake of Ca supplement (300 mg/day), together with 100 mg magnesium, 0.9 mg vitamin D3 and 19 mg vitamin K, could increase BMC and IGF-1, and tended to decrease BF, although there were no changes in BMI and LB, in teenage girls. This dose of Ca taken daily at a young age could beneficially affect growth hormone secretion and hopefully contribute to the risk reduction of prospective osteoporosis by increasing peak bone mass.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Abnormal central fat accumulation was recently reported to be reduced by growth hormone treatment, which would result in cardiovascular risk reduction at the optimal dose. 10 In conclusion, our study found that the intake of Ca supplement (300 mg/day), together with 100 mg magnesium, 0.9 mg vitamin D3 and 19 mg vitamin K, could increase BMC and IGF-1, and tended to decrease BF, although there were no changes in BMI and LB, in teenage girls. This dose of Ca taken daily at a young age could beneficially affect growth hormone secretion and hopefully contribute to the risk reduction of prospective osteoporosis by increasing peak bone mass.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, increased Ca results in osteoblastic proliferation that promotes further IGF‐1 secretion. Abnormal central fat accumulation was recently reported to be reduced by growth hormone treatment, which would result in cardiovascular risk reduction at the optimal dose 10 …”
Section: Discussionmentioning
confidence: 99%